Answer:
see explanation
Explanation:
The equation of a parabola in vertex form is
y = a(x - h)² + k
where (h, k) are the coordinates of the vertex and a is a multiplier
given a quadratic in standard form : y = ax² + bx + c : a ≠ 0
Then the x- coordinate of the vertex is
= -
![(b)/(2a)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/eoegn6mvxjwnsbs8qeqw3ayn0w36v7k5kl.png)
Rearrange 2v² - 12v - 29 = 3 into standard form ( subtract 3 from both sides )
2v² - 12v - 32 = 0 ← in standard form
with a = 2, b = - 12, hence
= -
= 3
substitute x = 3 into the equation for corresponding value of y
y = 2(3)² - 12(3) - 32 = 18 - 36 - 32 = - 50
vertex = (3, - 50)
y = 2(v- 3)² - 50 ← in vertex form